Functional, nutritional and social factors associated with mobility limitations in the elderly: a systematic review - José Rodolfo Torres de Araújo; Rafael Rodolfo Tomaz de Lima; Ila Maria Ferreira-Bendassolli; Kenio Costa-de Lima (Instituto Nacional de Salud Pública, 2018)
Objective. To systematically review the prevalence and incidence of mobility limitations in the elderly people and their associated factors. Materials and methods. Articles in the electronic literature were searched via PubMed, Scopus, Lilacs, SciELO, PAHO, MedCarib, Repidisca, Wholis, IBCES, PEDro, Medline and Bireme (2012-2016). The instrument STROBE was used to analyze the quality of the work and the PRISMA recommendation was used to structure the review. Results. Nine studies were included. The prevalence of mobility limitations ranged from 58.1 to 93.2% and the incidence ranged from 23 to 53.7%. Studies provided evidence of association of mobility limitations in the elderly population with high BMI, low 25-hydroxy vitamin D, sarcopenia, fragility, chronic pain, functional dependence, advanced age in women, low hip flexion, sedentary lifestyle, and social support difficulties. Conclusion. Mobility limitations in the elderly had high prevalence and incidence, and there was evidence of association with nutritional, functional and social factors.